A case of cervical dystonia with GNAL mutation and a subsequent shift in laterality of torticollis after temporary remission. Issue 1 (11th December 2020) - Itaya, Sakiko; Kawarai, Toshitaka; Kamata, Tomoyuki
Abstract: We report an adult case of cervical dystonia associated with a GNAL mutation. Torticollis first set in when the patient was 19 years old. The disease went into remission but subsequently recurred, with a change in laterality of the torticollis. For two years, the symptoms are managed by a combination of L‐DOPA, trihexyphenidyl, and botulinum toxin.